A Simple and Safe Anastomosis for Pancreatogastrostomy Using One Binding Purse-String and Two Transfixing Mattress Sutures. (27th February 2012) - Bartsch, D. K.; Langer, P.; Kanngießer, V.; Fendrich, V.; Dietzel, K.
Abstract : Pancreatic anastomotic leakage remains a persistent problem after pancreaticoduodenectomy (PD), especially in the presence of a soft, nonfibrotic pancreas. A modified technique for pancreatogastrostomy was devised, which combines one binding purse-string and two transfixing mattress sutures between the pancreatic stump and the posterior gastric wall. This technique was applied in 35 patients after PD for malignant and benign diseases of whom 10 (28.6%) had a soft pancreas. Median time for the anastomosis was 18 minutes. Operative mortality was zero, and morbidity was 34.3%. Three (8.6%) patients developed a pancreatic fistula (2 type A, 1 type B) as classified according to the International Study Group on pancreatic fistula. All fistulas resolved without further intervention. The described technique is a simple and safe reconstruction procedure after PD that warrants further evaluation.